Promoting Voice and Agency Among Forcibly Displaced Children and Adolescents: Participatory Approaches to Practice in Conflict-Affected Settings. (September 2021) - Wessells, Michael G.
Globally, large numbers of children and adolescents are displaced by armed conflict, which poses significant threats to their mental health, psychosocial well-being, and protection. Although humanitarian work to support mental health, psychosocial well-being, and protection has done considerable good, this paper analyzes how humanitarian action is limited by excessive reliance on a top-down approach. Although the focus is on settings of armed conflict, the analysis offered in this paper applies also to the wider array of humanitarian settings that spawn increasing numbers of refugees globally.